The Effectiveness of Tera Exercises, Healthy Heart Exercises and Elderly Exercises to Decrease Blood Pressure for Elderly - purwo, Purwo Susilo Nugroho; Soegiyanto, Soegiyanto; Nasuka, Nasuka (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2021)
Indonesian life expectancy has increased, and the number of elderly people is also getting bigger. This study aims to determine the effectiveness of tera exercises, healthy heart exercises, and elderly exercises on lowering blood pressure for 28 elderly, these exercises are done for 20 minutes. The elderly has an age of 60-90 years. The type and research design used in this study was a Quasi Experiment with pre-test and post-test design which has a level of p<0.00. This study was conducted on elderly women with a standard deviation of 133.85/85.56. All of the elderly before being given the tera exercise treatment were recorded to have an average systolic blood pressure of 145.96±9.2, on healthy heart exercise 141.82±11.6 and elderly exercise 138.5±17.6. Then measure blood pressure after doing exercise, on tera exercise it was 133.96±8, while on healthy heart exercise it was 28.39±14, and the average on elderly exercise was 139.18±8.6. Based on the result of the multiple linear regression test has a value of p<0.00. This means that giving exercise has a significant effect on reducing blood pressure in the elderly. The decrease of blood pressure on tera exercises has a value of 70%, in healthy heart exercises has a value of 90%, and in the elderly exercises has a value of 85%. Conclussion all of these exercises have significant values in reduced blood pressure for the elderly. The healthy heart exercise most significant influence in reduced blood pressure for the elderly.